DAMPAK ALIH FUNGSI LAHAN PERSAWAHAN TERHADAP PRODUKSI PADI DI DESA MANARAP BARU KECAMATAN KERTAK HANYAR KABUPATEN BANJAR - Rahmi Aufa Rusady; Danang Biyatmoko; Taufik Hidayat; Hilda Susanti (Universitas Lambung Mangkurat, 2014)
Economic growth requires a demand availability of land for infrastructure development. Though an increase in land productivity is strongly influenced by the amount of land used. Another factor that will disrupt food production is the conversion of agricultural land that led to the environmental degradation such as soil degradation of water quality, air pollution and other environmental damage. This research aims to determine the level of change that occurred in the area of land to non-agricultural paddy fields, determine the level of change in rice production, and to determine the factors that cause the occurrence of paddy land conversion to non-agricultural in Manarap Baru Village. This research is a survey which aims to test the hypothesis that there is data in the field by digging through direct interviews with farmers. The data analysis using questionnaires. The results showed that the Manarap Baru Village paddy fields decreased by 64.78 ha or about 3.47% per year and did not experience a reduction in rice production despite reduced their land. Rice production increased by 2.86% per year due to increased productivity of rice from 3.14 tons / ha in 2008 to 4.43 tons / ha in 2012. Major cause of rice land conversion to non-agricultural residential development that is driven by the dynamics of urban growth, increasing population growth, the state of the economy, and no area of government regulation.